A facile solvent-free and one-step route to prepare amino-phosphonic acid functionalized hollow mesoporous silica nanospheres for efficient Gd(III) removal. (10th January 2020) - Yin, Weiyan; Liu, Liangyi; Zhang, Haoyue; Tang, Sai; Chi, Ruan
Abstract: Gadolinium is known to be a most widely used but toxic rare-earth element, and Gd(III) ions exist in aqueous media will bring about serious damage to the ecosystem. However, few work on the application of adsorption strategy with enough high Gd(III) uptake is reported. Since the hollow mesoporous silica nanospheres (HMSNs) and amino-phosphonic acid (APA) compounds have shown inherent advantage for being used as effective adsorbent and chelating ligand in toxic metals adsorption due to their remarkable properties. Herein, we follow the cleaner production philosophy, proposing for the first time to modify the HMSNs nanomaterial with APA group by reacting phosphorous acid with cyano-functionalized hollow mesoporous SiO2 (CFHMSNs) via one-step reaction under solvent-free conditions, and apply to remove Gd(III) form wastewater. The obtained materials are characterized by a variety of techniques. Characterization results show that the APA-functionalized material (AFHMSNs) has ordered mesoporous structure, high stability and large surface area (825.3 m 2 /g). The maximum uptake of Gd(III) for AFHMSNs (387.3 mg/g) is much higher than those of the reported adsorbents because of the high surface area, and multifunctional chelating interactions of the adsorbent with Gd(III) ions. Gd(III) adsorption onto AFHMSNs can be well described by the Langmuir isotherm and pseudo second order kinetics model. The adsorption is chemical complexation mechanism which is proposed based on FTIR and XPS analysis. It is found for the first time that the adsorption of Gd(III) onto AFHMSNs slightly enhanced with the coexistence of Al 3+ in the relatively lower concentrations, which may be due to the synergistic effect of pseudo-boehmite. This work provides a favorable strategy to design and synthesis of hollow mesoporous nanomaterial with superior adsorption performances and potential for the cleanup of toxic metals from wastewater. Graphical abstract: Image 1 Highlights: The adsorbent was prepared via one-step reaction under solvent-free strategy. High adsorption capacity and rapid adsorption rate of Gd(III) were observed. The existence of lower concentrations Al 3+ can promote the Gd(III) adsorption. The adsorption mechanism may be explained by the chelation interaction.